Blood Transfusion Predicts Prolonged Mechanical Ventilation in Acute Stanford Type A Aortic Dissection Undergoing Total Aortic Arch Replacement - Xie, Qiang; Li, Chengnan; Zhong, Yongliang; Luo, Congcong; Guo, Rutao; Liu, Yongmin; Zheng, Jun; Ge, Yipeng; Sun, Lizhong; Zhu, Junming (Frontiers in Cardiovascular Medicine, 2022)
Background: This research aimed to evaluate the impacts of transfusing packed red blood cells (pRBCs), fresh frozen plasma (FFP), or platelet concentrate (PC) on postoperative mechanical ventilation time (MVT) in acute Stanford type A aortic dissection (ATAAD) patients undergoing total arch replacement (TAR). Methods: The clinical data of 384 ATAAD patients after TAR were retrospectively collected from December 2015 to October 2017 to verify whether pRBCs, FFP, or PC transfusion volumes were associated with postoperative MVT. The logistic regression was used to assess whether blood products were risk factors for prolonged mechanical ventilation in all three endpoints (PMV ≥24 h, ≥48 h, and ≥72 h). Results: Mean age of 384 patients was 47.6 ± 10.689 years, 301 (78.39%) patients were male. Median MVT was 29.5 (4-574) hours (h), 213 (55.47%), 136 (35.42%) and 96 (25.00%) patients with PMV ≥24 h, ≥48 h, and ≥72 h, respectively. 36 (9.38%) patients had no any blood product transfusion, the patients with transfusion of pRBCs, FFP, and PC were 334 (86.98%), 286 (74.48%), and 189 (49.22%), respectively. According to multivariate logistic regression of three PMV time-endpoints, Age was a risk factor (PMV ≥24 h odds ratio [ORPMV≥24] =1.045, p=0.005; ORPMV≥48=1.060, p=0.002; ORPMV≥72=1.051, p=0.011). pRBCs transfusion (ORPMV≥24=1.156, p=0.001; ORPMV≥48=1.156, p<0.001; ORPMV≥72=1.135, P≤0.001) and PC transfusion (ORPMV≥24=1.366, p=0.029; ORPMV≥48=1.226, p=0.030; ORPMV≥72=1.229, p=0.011) were independent risk factors for PMV. FFP had no noticeable effect on PMV (ORPMV≥48=0.999, 95% confidence interval [CI] 0.998-1.000, p=0.039; ORPMV≥72= 0.999, 95% CI 0.998-1.000, p=0.025). Conclusions: In ATAAD patients after TAR, the incidence of PMV was very high. Blood products transfusion was closely related to postoperative mechanical ventilation time. pRBCs and PC transfusions and age increased the PMV incidence in all three endpoints.